Reliability and validity of a modified 3-minute all-out swimming test in elite swimmers - Mitchell, L. J. G.; Pyne, D. B.; Saunders, P. U.; Rattray, B. (European Journal of Sport Science, 2018)
Critical speed (CS) testing is useful in monitoring training in swimmers, however, completing a series of time trials (TTs) regularly is time-consuming. The 3-minute test may be a solution with positive initial findings. This investigation examined whether a modified 3-minute test (12 × 25 m) could assess CS and supra-CS distance capacity (D`) in swimmers. A series of 12 × 25 m intervals were completed unpaced at maximal effort, interspersed with 5 s rest periods. The model speed = a eb t + c was fitted to the data and integrated to calculate D`. The slowest two of the last four efforts were averaged to calculate CS. To assess reliability, 15 highly trained swimmers (9 females, 6 males) completed the 12 × 25 m twice within 72 h. Four measures were deemed reliable: peak velocity (0.01 m s-1; 0.5%, typical error and % coefficient of variation), CS (0.02 m s-1; 1.2%), D` (1.22 m; 5.7%) and drop off % (0.70% points; 4.5%). To assess criterion validity, 21 swimmers (9 from reliability, 12 other) completed two competition races within 2 weeks of a 12 × 25 m in the same stroke. Traditional CS and D` measures were calculated from competition performances (TT method). TT CS and 12 × 25 m CS were highly correlated (adj. R2 = 0.92, p < .001). D` values were moderately correlated (adj. R2 = 0.60, p < .01). Two TTs may have been too few to estimate D` accurately. The 12 × 25 m all-out swimming test is a reliable method for assessing CS and D` in swimmers, however, the validity of D` requires further investigation.